Constraining Paleoseismicity of the Wulashan Piedmont Fault on the Northern Margin of the Ordos Block From Fault Scarp Morphology - Bi, Haiyun; Shi, Lin; Zhang, Dongli; Peng, Hui; Yang, Jingjun; You, Zicheng; Sun, Xin (Frontiers in Earth Science, 2022)
Fault scarps preserve important information about past earthquakes on a fault, and thus can be applied to investigate the fault slip histories and rupture patterns. In this study, the morphology of fault scarps was used to constrain the paleoseismicity of the Wulashan Piedmont Fault located on the northern margin of the Ordos Block based on high-resolution LiDAR topography. We constructed the vertical displacement distribution of the fault through measuring the heights of a large number of scarp profiles extracted on different geomorphic surfaces along the fault. Through statistical analysis of the dense collection of vertical displacement dataset, a total of seven paleoseismic events were identified which followed a characteristic slip pattern with an average slip of ~1.0 m. We further detected slope breaks in the fault scarp morphology to quantify the number of paleoearthquakes that occurred on the scarps, and discriminated at least five individual surface-breaking events. Both the number and slip of paleoearthquakes recognized from the morphology of fault scarps were in good agreement with previous paleoseismic trenching records. Based on the empirical scaling relationship between moment magnitude and rupture parameters, a moment magnitude of Mw 6.7~7.5 was determined for the paleoearthquakes occurred on the fault. With the fault slip rate derived by previous studies, we estimated an average recurrence interval of 1.3~1.8 kyr for the paleoseismic events, which is very close to the elapsed time since the most recent earthquake, indicating a high potential seismic hazard on the Wulashan Piedmont Fault.